Decitabine Compared with Low-Dose Cytarabine for the Treatment of Older Patients with Newly Diagnosed Acute Myeloid Leukemia: A Pilot Study of Safety, Efficacy, and Cost-Effectiveness. (4th November 2015) - Jacob, Linu A.; Aparna, S.; Lakshmaiah, K. C.; Lokanatha, D.; Babu, Govind; Babu, Suresh; Appachu, Sandhya
Abstract : Introduction . The incidence of Acute Myeloid Leukemia (AML) increases progressively with age and its treatment is challenging. This prospective case control study was undertaken to compare the safety, efficacy, and cost-effectiveness of decitabine with those of cytarabine in older patients with newly diagnosed AML who are not fit for intensive chemotherapy. Materials and Methods . 30 eligible patients above 60 years old with newly diagnosed AML were assigned to receive decitabine or cytarabine. The primary end point was overall survival (OS). The secondary objective was to compare adverse events and cost-effectiveness of therapy in the two study groups. Results . In this study, 15 patients received decitabine and 15 patients received cytarabine. The median OS was 5.5 months for each of the treatment groups. The hazard ratio between the treatment groups was 0.811 with 95% CI of 0.390 to 1.687. Toxicity profile was similar in both groups. Cost per cycle of chemotherapy in INR was 24, 200 for decitabine and 1, 600 for low-dose cytarabine group. Median of simplified cost-effectiveness ratio was 0.00022 for decitabine group and 0.0034 for low-dose cytarabine group. Conclusions . For elderly patients with AML, decitabine and low-dose cytarabine should be chosen based on the patient's choice and affordability. Our study has shown that both of these agents have similar OS and toxicity. Low-dose cytarabine scores over decitabine in developing countries as it is more cost-effective.